Pansteatitis in tilapia (Oreochromis mossambicus) from Loskop Dam, South Africa : links between the environment, diet and thyroid status - Oberholster, Paul Johan (University of Pretoria, 2016)
Thesis (PhD)--University of Pretoria, 2014.